TOEFL iBT insider : (Tổng hợp Thành phố Hồ Chí Minh, 2008)
LinguaForum's TOEFL iBT Insider is a complete guide to get a full range of materials offering innovative and effective study solutions to fully prepare you for the TOEFL iBT. Developed by the world's leading publisher of TOEFL preparation materials, TOEFL iBT Insider provides learners with a complete understanding of all the iBT TOEFL sections and what is expected of takers, as well as to provide students with useful skills and strategies for meeting those expectations.